Biomechanically induced regulation of Damage-Regulated Autophagy Modulator 1 in periodontal cells and tissues - Mannes, Anemone; Nogueira, Andressa; Both, Annika; Mayr, Alexandra; Marciniak, Jana; Küchler, Erika Calvano; Bekbulat, Fazilet; Cirelli, Joni A. [UNESP]; Kirschneck, Christian; Behl, Christian; Deschner, James; Jäger, Andreas; et al. (Elsevier, 2025)
Purpose: Autophagy is an important adaptive process for mechanotransduction, in which Damage-Regulated Autophagy Modulator 1 (DRAM1) has a key function in cell fate determination. This study aimed to analyze the influence of biomechanical loading on DRAM1 expression in periodontal cells and tissues. Methods: Human periodontal ligament (PDL) fibroblasts were stimulated with different pressure protocols, physiological load and overload, in the presence and absence of autophagy inhibitor 3-methyladenine (3-MA) and compared with untreated cells. DRAM1 expression was measured using real-time PCR and ELISA after 1 d and 2 d. DRAM1 expression was determined in gingival biopsies of rats, and gene expression of DRAM1 was analyzed after 1 d, 7 d, and 15 d of orthodontic treatment. Statistical analysis was carried out using ANOVA and post-hoc tests. Results: Overload led to increased DRAM1 gene expression after 1 d, while physiological load did not change DRAM1 expression. After 2 d, DRAM1 expression was increased in both groups. Protein levels were elevated after 2 d of pressure application of both magnitudes, while no significant increase was evident after 1 d. Treatment with 3-MA led to a significant reduction in DRAM1 gene expression in both pressure groups, while it remained unchanged in the control group. In vivo, DRAM1 was located in the periodontal ligament, and we could determine an orthodontic force-mediated increase in DRAM1 gene expression at 7 d and 15 d. Conclusion: This study indicates a dependence of DRAM1 regulation on the duration and magnitude of bio-mechanical loading and on autophagy-associated pathways.
Keywords: Autophagy; Damage-regulated autophagy modulator; Load; Orthodontic force application; Overload; Periodontal ligament